2020
DOI: 10.1021/acs.analchem.0c02343
|View full text |Cite
|
Sign up to set email alerts
|

Combining Mass Spectrometry of Picoliter Samples with a Multicompartment Electrodynamic Trap for Probing the Chemistry of Droplet Arrays

Abstract: Single droplet levitation provides contactless access to the microphysical and chemical properties of micron-sized samples. Most applications of droplet levitation to chemical and biological systems use non-destructive optical techniques to probe droplet properties. To provide improved chemical specificity, we couple a multi-compartment quadrupole electrodynamic trap (QET) to single droplet mass spectrometry. Our QET continuously traps a monodisperse droplet population (∼10's -100's of droplets), and allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 77 publications
(151 reference statements)
2
32
0
Order By: Relevance
“…confines charged droplets along the axis of the quadrupole trapping electrodes, and is described in Willis et al, 50 and Jacobs et al 51 Aqueous micron-sized droplets are generated with a piezoelectric droplet with the aid of a humidity-controlled gas flow (Fig. S1).…”
Section: Quadrupole Electrodynamic Trap the Branched Quadrupole Elect...mentioning
confidence: 99%
See 1 more Smart Citation
“…confines charged droplets along the axis of the quadrupole trapping electrodes, and is described in Willis et al, 50 and Jacobs et al 51 Aqueous micron-sized droplets are generated with a piezoelectric droplet with the aid of a humidity-controlled gas flow (Fig. S1).…”
Section: Quadrupole Electrodynamic Trap the Branched Quadrupole Elect...mentioning
confidence: 99%
“…Two complementary ionization sources are used in these experiments: paper spray ionization 50,54,55 and thermal desorption coupled to helium glow discharge ionization. 50,56 Development and use of these ion sources for detection of single micron-sized droplets is described in detail in Jacbos et al, 51 Kohli & Davies 54,55 and Willis et al 50 Their operation is summarized below.…”
Section: Single Droplet Ambient Ionization Mass Spectrometry All Meas...mentioning
confidence: 99%
“…Vibrational sum frequency generation spectroscopy (SFG), Fourier transform infrared spectroscopy (FTIR), and fluorescence spectroscopy, which are also non-destructive, could be complementary to Raman in probing the chemical composition of single particles. Recently, novel combination of EDB and mass spectrometry was reported, which can directly introduce the trapped particle for mass spectrometry analysis (Jacobs et al, 2017;Birdsall et al, 2018;Willis et al, 2020). Adoption of this technique with Raman to form an EDB-Raman system with subsequent MS analysis is relatively straightforward.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, novel combination of EDB and mass spectrometry was reported, which can directly introduce the trapped particle for mass spectrometry analysis. (Birdsall et al, 2018;Willis et al, 2020;Jacobs et al, 2017) suggested. (Li et al, 2010;Anema et al, 2011) l Multiphase reaction studies based on single-particle Raman spectroscopy.…”
Section: Bioaerosolsmentioning
confidence: 99%